Integrated analysis of lncRNA and mRNA for the apoptosis of porcine ovarian granulosa cells after polyphenol resveratrol treatment - Zhang, Huibin; Liu, Yangguang; Han, Zheng; Xu, Qilong; Zhang, Nannan; Wang, Jinglin; Zheng, Xianrui; Ding, Yueyun; Yin, Zongjun; Zhang, Xiaodong (Frontiers in Veterinary Science, 2023)
Resveratrol (RES) is a non-flavonoid polyphenol compound that can be involved in follicular development and ovulation. However, the mechanism by which resveratrol regulates the apoptosis of porcine ovarian granulosa cells (POGCs) through long non-coding RNA (lncRNA) is poorly understood. We generated POGCs models of different doses of RES (0, 25, 50, 75, and 100 μM). It was observed that the cell viability was the highest in the 50 μM group, and the highest apoptosis rates were recorded in the 100 μM group. Therefore, a control group (n = 3, 0 μM RES group), a low RES group (n = 3, 50 μM RES group), and a high RES group (n = 3, 100 μM RES group) of POGCs were created for next RNA sequencing. Gene Ontology (GO) indicated that differentially expressed lncRNAs associated with apoptotic process were highly enriched. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of lncRNA target genes found that the Wnt signaling pathway and PI3K-Akt signaling pathway were both enriched. Furthermore, we constructed lncRNA-mRNA networks related to Metabolic and Cell Apoptosis, respectively. In the networks, five key-lncRNAs were screened, which may play a significant role in the process of POGCs metabolism and apoptosis. Furthermore, we focused on the function of a lnc-GAM (lncRNA associated with Granulosa cells Apoptosis and Metabolism) and verified that lnc-GAM could influence cell apoptosis in POGCs development by affecting the mRNA expression of apoptosis-related markers, and also affects the secretion of steroid hormones and related genes expression in POGCs cultured in vitro. Our study provides seminal data and important new insights into the regulation of reproductive mechanisms in porcine and other female mammals.